Günstige Aufkommensperspektiven - Steuererhöhungen nicht erforderlich - Heinz Gebhardt; Rainer Kambeck (Wirtschaftsdienst, 2013)
Nach der aktuellen Prognose des Arbeitskreises 'Steuerschätzungen' wird das Steueraufkommen von 600 Mrd. Euro 2012 bis zum Jahr 2017 auf knapp 705 Mrd. Euro steigen. Verfügt der Staat damit über ausreichend hohe Finanzmittel, so dass sich sogar Spielräume für Steuersenkungen bieten? Die Parteien bieten dazu unterschiedliche Konzepte, in denen zum Teil deutliche Steuererhöhungen gefordert werden. – – In May 2013, the Working Party on Tax Revenue Forecasting presented its new estimate, which is based on the federal government's spring projection of the medium-term development of the overall economy. Tax revenues are estimated to expand from 600 bn in 2012 to 704.5 bn in 2017. Because the tax revenues increase at a faster pace than the nominal GDP, the tax-to-GDP ratio increases from 22.7% to 23.1%. Contrary to the diagnosis of the opposition parties in the German Bundestag, we see no structural revenue gap. In fact, public budgets will realise structural surpluses in the coming years if governments are successful in constraining expenditure growth. There are no convincing reasons to increase public revenues by increasing tax rates or launching new fees; in both cases tax burdens would increase and that would dampen economic growth. Instead, there will be budgetary leeway to reduce the fiscal drag if governments are committed to a sound consolidation policy
Keywords: H20; H62; H71; 330; Steuereinnahmen; Prognose; Steuersenkung; Steuererhöhung; Parteipolitik; Deutschland